2017
DOI: 10.1007/s00128-017-2120-8
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Flame Retardants in House Dust from South China and Related Human Exposure Risks

Abstract: House dust associated with organic pollutants is not only a potential source of pollutants to the outdoor environment, but also a source to human exposure. The present study investigated the occurrence and concentrations of organophosphate flame retardants (OPFRs) in house dust collected from South China dwellings (n = 20). The results revealed a universal presence of most target OPFRs in house dust, with concentrations of ΣOPFRs ranging from 2.06 to 19.95 μg/g. The median concentration of ΣOPFR (9.20 μg/g) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Gunderson et al reported that the mean daily intake of TBEP in infants and juveniles could be estimated at 0.2‐14.4 ng/kg/day (Gunderson, 1988, 1995a, 1995b), which is analogous to the low dose of TBEP used in our study. Tan and his colleagues showed that the estimated daily intake of OPFRs for toddlers is 31.7 and 127 ng/kg/day under the average and high exposure scenarios, respectively, which are much greater than those for PBDEs (Tan et al, 2017). Furthermore, Fromme et al reported that the daily intake of 10 OPFRs derived from dust and air for children is estimated to be 3.2 μg/kg/day, and TBEP was most abundant among OPFRs (Fromme et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Gunderson et al reported that the mean daily intake of TBEP in infants and juveniles could be estimated at 0.2‐14.4 ng/kg/day (Gunderson, 1988, 1995a, 1995b), which is analogous to the low dose of TBEP used in our study. Tan and his colleagues showed that the estimated daily intake of OPFRs for toddlers is 31.7 and 127 ng/kg/day under the average and high exposure scenarios, respectively, which are much greater than those for PBDEs (Tan et al, 2017). Furthermore, Fromme et al reported that the daily intake of 10 OPFRs derived from dust and air for children is estimated to be 3.2 μg/kg/day, and TBEP was most abundant among OPFRs (Fromme et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…-Organic emissions from PU materials in the context of human health and exposure are investigated -Reported VOC and SVOC concentrations from PU insulation and household materials are reviewed -OFRs are emitted in the long term and are found abundantly indoors even in buildings with no PU insulation -Amines impact perceived IAQ, but it's unclear which PU compound/s impact health individually or cumulatively , 1987IPCC, 2013IPCC, , 2014EU, 2014;EPA, 2016;Australian Government, 2017) concentration of all studies. (Stapleton et al, 2009;Ali et al, 2012Ali et al, , 2018Fromme et al, 2014;He et al, 2015;Hammel et al, 2017;Tan et al, 2017;Bi et al, 2018;Deng et al, 2018)…”
Section: Highlightsmentioning
confidence: 99%
“…Concentration of TDCPP in cars (Brommer et al, 2012;Cristale et al, 2018) was found to be 14-2,280 times higher than the concentration in buildings as per Appendix C. The mean concentrations of flame retardants in dust from 13 studies in 7 countries from indoor spaces (n=502) are plotted in Figure 7. (Stapleton et al, 2009;Ali et al, 2012Ali et al, , 2018Fromme et al, 2014;He et al, 2015;Hammel et al, 2017;Tan et al, 2017;Bi et al, 2018;Deng et al, 2018) Figure 7 shows that the mean concentration of TCPP in settled dust is 3010 ng/g, of TCEP is 1895 ng/g and of TDCPP is 1844 ng/g based on 502 indoor samples from four continents.…”
Section: Flame Retardantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is easy for OPEs to enter the environment through volatilization, product wear, leakage and other ways in the process of production, transportation and use, because OPEs was added in the material by physical addition rather than chemical bonding (Gao et al, 2014). At present, OPEs widely existed in water (Kim et al, 2018;Yin et al, 2021), soil (Yin et al, 2016;Yang et al, 2018), outdoor air (Yin et al, 2020;Javier et al, 2016) and indoor (Tan et al, 2017) environment, even in many kinds of animals and plants (Wan et al, 2017;Strobel et al, 2018), human urine (Schindler et al, 2009) and breast milk (Sundkvist et al, 2010). Unfortunately, previous studies have demonstrated that some OPEs have the characteristics of carcinogenesis, neurotoxicity and reproductive toxicity that may bring risks to human health (Kim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%